De la rage métaphysique au calme scientifique : religion et sciences naturelles chez Flaubert - Juliette Azoulai (Flaubert: Revue Critique et Génétique)
In his correspondence Flaubert never ceases to praise the natural sciences as a remedy against metaphysicians’ and theologians’ “rage to conclude” and thus as a healing method, through the study of facts in themselves, independent of any analysis of root and final causes. However, Flaubert’s characters, confronted with the naturalist’s knowledge, are far from reaching any ataraxic wisdom and, on the contrary, appear to be overwhelmed by intense feelings and emotions: terror, fear and fascination. The study of Nature forces Flaubert’s characters to face an experience of totality that underlines their finitude and opens onto infinity. Thus it offers an experience that belongs to the sacred, so that the natural sciences, far from being opposed to Metaphysics, lead to the understanding of an “immanent surnaturalism”, to use one of Victor Hugo’s expressions, which is a combination of grotesque irrationality and sublime wisdom.